Epidemiological and clinical profile of vulvovaginitis at the University Clinics of Kisangani City (Tshopo Province), Democratic Republic of the Congo - David Kpangamogo Dawili; Ruphin Djoza Djolu; Modeste Modeawi Ndaba; De Rosaine Augustin Moleke; Colette Ashande Masengo; Monizi Mawunu; Emmanuel Likwekwe Komanda; Koto- (Orapuh, Inc., 2024)
Introduction Vulvovaginitis is an inflammation that affects both the vulva (the external part of the female genital organs) and the vagina. It can be caused by various factors such as bacterial, fungal, or viral infections, allergic or irritative reactions, or hormonal imbalances. Common symptoms include itching, burning, redness, pain, and abnormal vaginal discharge. Purpose This study aimed to examine the epidemiological and clinical approach to vulvovaginitis at the University Clinics of Kisangani during the years 2012-2014. Methods The study included a total of 1,966 patients admitted to the Gynaecology and Obstetrics Department during the study period. Data on age, marital status, education level, occupation, and residential area were collected. Information on antecedent infections, presenting symptoms, and causative agents was also gathered. Statistical analysis was performed to determine the prevalence and distribution of vulvovaginitis cases. Results Out of the total patients, 298 (15.2%) were diagnosed with vulvovaginitis. Most cases were aged between 20-24 years (29.9%), followed by 15-19 years (25.8%), and 25-29 years (17.1%). Most cases were married (55.4%) and had secondary education (46%). Housewives accounted for the highest proportion of cases (44.63%). Makiso had the highest number of cases (54%), followed by Mangobo (25.2%). The most common antecedent infection was vaginal candidiasis (46.3%), and the most common presenting symptom was abnormal genital discharge (37.2%). Candida albicans was the most common causative agent (46.64%), followed by Neisseria gonorrheae (26.84%) and Trichomonas vaginalis (22.48%). Other agents were Chlamydia trachomatis (1.67%), Haemophilus ducreyi (1%), human papillomavirus (HPV), and herpes simplex virus (HSV) (0.67% each). Conclusion Vulvovaginitis is a common condition at the University Clinics of Kisangani, affecting a significant proportion of women. The findings highlight the need for further research and education on the prevention and management of vulvovaginitis in this population.